2017
DOI: 10.14419/ijdr.v5i2.8343
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of various administrative techniques of methylprednisolone on oedema, trismus and pain after lower third molar surgery

Abstract: Due to their anatomical position, the surgical removal of impacted third molars results in oedema, pain, and trismus. The purpose of this study was to evaluate the efficacy of four different routes of administration of methylprednisolone on oedema, trismus and pain after lower third molar surgery. This randomized, perspective, and controlled study included 150 patients. The patients were randomly divided into five groups: Group A (control; no steroids), Group B (Submucosal injection), Group C (oral tablets), G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
1
2
1
Order By: Relevance
“…Although there was marked increase in pain reported by the patients of control group and least in IM group, there was no statistically significant difference in mean pain score between control , IM, IV and oral group (p=.270). Our results somewhat differed from results of Vaibhav et al 20 as the mean pain score was significantly different on 7 th postoperative day. On 14 th post op day in our study, with respect to control group, all other groups proved to be better in terms of mean pain score while IM, IV and Oral group provided almost similar results (with a negligible difference of 0.08 on VAS score).…”
Section: Paincontrasting
confidence: 99%
See 2 more Smart Citations
“…Although there was marked increase in pain reported by the patients of control group and least in IM group, there was no statistically significant difference in mean pain score between control , IM, IV and oral group (p=.270). Our results somewhat differed from results of Vaibhav et al 20 as the mean pain score was significantly different on 7 th postoperative day. On 14 th post op day in our study, with respect to control group, all other groups proved to be better in terms of mean pain score while IM, IV and Oral group provided almost similar results (with a negligible difference of 0.08 on VAS score).…”
Section: Paincontrasting
confidence: 99%
“…Intra-group comparison of mean pain score at 3 rd day was done between the groups. There was no significant difference in mean pain score between control, IM, IV and oral group (p=0.119) the result of our study was similar to results in study of Vaibhav et al 20 .…”
Section: Painsupporting
confidence: 90%
See 1 more Smart Citation
“…However, no comparative analysis between SM and IV or IM routes could be carried out due to a lack of studies. Mukund et al ( 39 ) in a trial comparing oral, SM, IV, and intramasseteric administration of MP reported better outcomes with the intramasseteric route after third molar surgeries. On the other hand, Selvaraj et al ( 40 ) did not find any difference in outcomes between intramasseteric and IM injections of MP at the gluteal region.…”
Section: Discussionmentioning
confidence: 99%